Consumers' food safety risk perceptions and willingness to pay for fresh-cut produce with lower risk of foodborne illness. (April 2018) - Yu, Heyao; Neal, Jack A.; Sirsat, Sujata A.
Abstract: There has been an increasing number of foodborne illness outbreaks associated with fresh and fresh-cut produce recently; however, few studies have examined consumers' risk perceptions and their willingness to pay (WTP) for fresh-cut produce with lower foodborne illness risk (FBIR). Hence, the objectives of this study were to examine how consumers perceived different food safety risk factors associated with fresh-cut produce and explore the factors associated with consumers' WTP for the fresh-cut produce with lower FBIR. The results showed that consumers' risk perception of foodborne pathogens was significantly lower than that of pesticides, which was mainly because consumers with optimistic bias perceived a very low probability of the occurrence of foodborne illness related to fresh-cut produce. The analysis of variance (ANOVA) indicated that millennial and female consumers had higher risk perceptions compared to other demographic groups. In addition, the WTP data demonstrated that the majority of consumers were willing to pay a premium for fresh-cut produce with lower FBIR. Millennial consumers with high-risk perceptions of pathogens and high fresh-cut produce purchasing frequency were more willing to pay a premium. The results provide useful information for fresh-cut produce processors to make decisions on enhancing the compliance of food safety practices. In addition, the results suggest that food safety regulatory agencies that develop public education materials should include information to reduce consumers' optimistic bias and enhance consumers' awareness of the risks associated with foodborne pathogens related to fresh-cut produce. Highlights: Consumers perceive unlikely that fresh-cut produce contain foodborne pathogens. Millennial and female consumers hold higher risk perceptions of fresh-cut produce. Majority of consumers are willing to pay a premium to reduce food safety risk. Millennial consumers with higher risk perception are more likely to pay for a premium.